Public relations activities of two community schools in the division of Bulacan - Forbes, Jose D. 1907- ([Quezon City s.n.], 1958)
The purpose of this study is to determine the public relations activities undertaken by the teachers and school administrators in Polo Central (poblacion) and Torres Bogallon (barrio) community schools. This was made to enable suggestions for improvement in the existing program, if any, of these schools and to point how the program may influence other community schools.
Thesis (M.Ed.)--University of the Philippines, 1958
Typewritten
Vita.
Keywords: Rural schools -- Philippine Islands -- Bulacan; Rural schools -- Public relations